2017
DOI: 10.1002/aoc.4184
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of meso‐substituted pyrazolyl porphyrin complexes and their highly active catalyst for oxidation of alkylbenzenes

Abstract: During the past few years, a great deal of effort has been devoted to the anchoring of catalytic oxidation. In this work, three new catalysts CuPp, MnPp and ZnPp by solvothermal methods with 5, 10, 15, 20‐tetrakis(4‐N‐pyrazolyl)‐phenyl porphyrin (H2Pp) and the corresponding metal salts have been synthesized and structurally characterized. The single crystal structures determined by X‐ray diffraction show the bond distances of M‐N in porphyrin cores determined the conformation of porphyrin rings. We explored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…immobilized metalloporphyrins and their catalysis systems [31][32][33][34][35] adapting to the cleaner production process. However, the resulting yields (acetophenone and phenylethanol (ONE + OL), less than 25%) were lower than those obtained from the catalytic systems above [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . In addition, RSM was also seldom used in the catalytic field of metalloporphyrins [14][15][16][17]19,20,[31][32][33][34][35] .…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…immobilized metalloporphyrins and their catalysis systems [31][32][33][34][35] adapting to the cleaner production process. However, the resulting yields (acetophenone and phenylethanol (ONE + OL), less than 25%) were lower than those obtained from the catalytic systems above [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . In addition, RSM was also seldom used in the catalytic field of metalloporphyrins [14][15][16][17]19,20,[31][32][33][34][35] .…”
mentioning
confidence: 75%
“…For promoting the catalytic activity and the re-usability of metalloporphyrins, and increasing the yields (ONE + OL) of ethylbenzene oxidation catalyzed by the immobilized metalloporphyrins catalysis systems, by investigation of the relative references, we found that, (1) the electron-withdrawing-groups metalloporphyrin grafted and coordinated to porous support could comprehensively enhance the catalytic activity and the re-usability for ethylbenzene oxidation 13 15 , 17 , 19 , 20 ; (2) the axial coordination action exerted the most important effect on the catalytic activity, and the covalent grafting action had a decisive effect on the increase of the total turnover frequencies (TOFs) and on the re-usability of the catalyst 36 ; (3) the most key internal effecting factor on the catalytic activity of the immobilized metalloporphyrin was the axial coordination action 37 ; (4) chitosan could be made into nanoporous support material and could provide ammonia groups for the graft and coordination of some metalloporphyrins 34 36 . Especially, it is cheap and no harm to our environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Yao et al [151] reported the synthesis of three novel catalysts (CuPp, MnPp, and ZnPp) by solvothermal methods and measured their catalytic activity in terms of alkylbenzene conversion. The catalysts exhibited better activities for ethylbenzene oxidation and selectivity towards acetophenone.…”
Section: mentioning
confidence: 99%
“…[35][36][37] Nevertheless, some reported POMOCs used in the catalytic oxidation of C-H bonds have the disadvantages of long reaction time and low selectivity. 38,39 1) (H 3 trz = 1,2,4-triazole) was designed and constructed under hydrothermal conditions and thoroughly characterized using single crystal X-ray diffraction, PXRD, TGA, FT-IR spectroscopy, and XPS. The stable complex 1 showed excellent catalytic performance as a heterogeneous catalyst in the oxidation of diphenylmethane.…”
Section: Introductionmentioning
confidence: 99%